Collaborative robotics and its paradigms for industrial manipulators - Weng, Ching-Yen (Nanyang Technological University, 2021)
Industrial robots can be applied to a wide range of feasible applications through various levels of programming and integration into manufacturing systems. By the cooperation between various agents, various collaborative patterns can be introduced to achieve their industrial objectives and improve many aspects of the task performance, such as time-efficiency, dexterity, and flexibility. Although this concept has been largely studied, it is too novel to be systematically defined in recent studies, especially for the use cases of industrial applications, leading to the difficulties of mature continuous integration and continuous delivery in manufacturing. To enable the design of industrial manipulators to be collaborative with other agents, such as other robotic systems or humans, a promising method is expected to turn such an abstract concept into a mathematical model so that the existed technologies of performance assessment can be applied to evaluate the deployment of systems. In addition, to consider both the precision and flexibility in human-robot collaboration for the industrial manipulators, to propose a unified framework to cover the contents of collaborative manipulation would support a more effective task execution with human-robot collaboration.